Ανασκαφή νεολιθικού οικισμού Θέρμης: ανασκαφική περίοδος 1987 - Γραμμένος Δ. Β.; Παππά Μαρία; Ούρεμ-Κώτσος Ντ.; Σκουρτοπούλου Κατερίνα; Γιαννούλη Ευτ. Γ.; Τσιγαρίδα Μπεττίνα (Μακεδονικά, 1989)
No Abstract